Hysteretic shear flexure interaction model of reinforced concrete columns for seismic response assessment of bridges. - Xu, Shi-Yu (Earthquake engineering & structural dynamics.)
This paper presents the methodology, model description, and calibration as well as the application of a coupled hysteretic model to account for nonlinear shear?flexure interactive behavior of RC columns under earthquakes, a critical consideration for seismic demand evaluation of bridges. The proposed hysteretic model consists of a flexure and a shear spring coupled at element level, whose nonlinear behavior are governed by the primary curves and a set of loading/unloading rules to capture the pinching, stiffness softening, and strength deterioration of columns due to combined effects of axial load, shear force, and bending moment. The shear?flexure interaction (SFI) is considered both at section level when theoretically generating the primary curves and at element level through global and local equilibrium. The model is implemented in a displacement-based finite element framework and calibrated against a large number of column specimens from static cyclic tests to dynamic shake table tests. The numerical predictions by the proposed model show very good agreement with experimental data for both flexure- and shear-dominated columns. The application of the proposed model for seismic assessment of bridges has been successfully demonstrated for a realistic prototype bridge. The factors affecting the SFI and its significance on bridge system response are also discussed.